Umroh Advance Funds in the View of Sharia Economic Law: Study on the Syakira Tour Hajj & Umrah travel in Bekasi City - Fikri Mauludi; Rahmad Hakim; Arif Luqman Hakim; Akbar Sarif (Iqtishodia: Jurnal Ekonomi Syariah, 2026)
Syakira Tour & Travel is a travel agency that provides Umrah and Hajj travel agencies in Bekasi City. Implementation of the Umrah bailout program at Syakira tour & travel to make it easier for prospective pilgrims who want to carry out the Umrah pilgrimage quickly. This research focuses on describing how Syakira Tour implements the Umrah Bailout Fund program for prospective pilgrims. The research method used is a qualitative method with a descriptive type, using interview techniques, observation and documentation. Determining the subject is based on who knows the information needed by the researcher. And the data analysis used uses data reduction models, data presentation and conclusions. The research location is at the Travel Hajj & Umrah Syakira Tour Bekasi. In this research, data analysis uses the interactive analysis model of Miles, Huberman & Saldana. The results of the research conclude that Umrah funding is permissible in view of sharia economic law, as long as prospective pilgrims fulfill the conditions that have been set, such as having good character, good managerial skills, and stable economic conditions. Practice of Umrah funding at PT. Syakira Asfarina Bekasi City was carried out by Amitra (a sharia bank) purchasing Umrah packages in cash from Travel. Prospective pilgrims can go to the travel agency or financing agency first. Regarding the fulfillment of the conditions for obtaining bailout funds is the decision of the financing party.